2009
DOI: 10.1002/btpr.269
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a recombinant autolytic wine yeast strain overexpressing the csc1‐1 allele

Abstract: During the aging step of sparkling wines and wines aged on lees, yeast cells kept in contact with the wine finally die and undergo autolysis, releasing cellular compounds with a positive effect on the wine quality. In view of the interest of autolysis for wine properties, biotechnologists have tried to improve autolytic yield during winemaking. In this work we used genetic engineering techniques to construct an autolytic industrial strain by expressing the csc1-1 allele from the RDN1 locus. The expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…There is great interest in correlating potential interactions between mannoproteins and tannins in red wines with desirable changes in sensory characteristics, for example, astringency, texture, and mouthfeel . Genetic interventions have also been reported that increase the release of mannoproteins in laboratory and industrial strains of S. cerevisiae , .…”
Section: Introductionmentioning
confidence: 99%
“…There is great interest in correlating potential interactions between mannoproteins and tannins in red wines with desirable changes in sensory characteristics, for example, astringency, texture, and mouthfeel . Genetic interventions have also been reported that increase the release of mannoproteins in laboratory and industrial strains of S. cerevisiae , .…”
Section: Introductionmentioning
confidence: 99%
“…Other authors addressed the expression of extracellular hydrolytic enzymes from different origins, mostly to help the release of primary aroma compounds from odourless precursors and improve mechanical properties of the juice and mass to ease extraction processing (Pérez‐González et al ., 1993 ; Ganga et al ., 1999 ). Another common type of genetic modification was changing the expression levels of S. cerevisiae genes to achieve improvements in secondary aroma, autolysis, or mannoprotein release (Lilly et al ., 2000 ; Lilly et al ., 2006 ; Tabera et al ., 2006 ; Cebollero et al ., 2009 ; González‐Ramos et al ., 2009 ). But none of these efforts directly led to new commercial starter cultures.…”
Section: Genetic Improvement Of Wine Yeastsmentioning
confidence: 99%
“…In the past, the growing demand for wine strains with specific technological characteristics led to the proposal of numerous engineered strains for various applications but, despite this, only a few cases have passed the laboratory scale (Pérez-González et al, 1993;González-Candelas et al, 1995, 2000Michnick et al, 1997;Schoeman et al, 1999;Lilly et al, 2000;Swiegers et al, 2007;Herrero et al, 2008;Cebollero et al, 2009). In almost all cases they are transgenic strains where one or more genetic determinants, derived from different organisms, were inserted into the host S. cerevisiae genome.…”
Section: Introductionmentioning
confidence: 98%